2021
DOI: 10.1186/s12974-020-02059-x
|View full text |Cite
|
Sign up to set email alerts
|

Microglial inflammation after chronic spinal cord injury is enhanced by reactive astrocytes via the fibronectin/β1 integrin pathway

Abstract: Background After spinal cord injury (SCI), glial scarring is mainly formed around the lesion and inhibits axon regeneration. Recently, we reported that anti-β1 integrin antibody (β1Ab) had a therapeutic effect on astrocytes by preventing the induction of glial scar formation. However, the cellular components within the glial scar are not only astrocytes but also microglia, and whether or not β1Ab treatment has any influence on microglia within the glial scar remains unclear. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 47 publications
0
29
0
Order By: Relevance
“…BV-2 is a commonly used microglial cell line that has been widely used in vitro experiments to explore inflammatory responses in many studies ( Riedl et al, 2009 ; Basso et al, 2017 ; Yoshizaki et al, 2021 ). The BV-2 microglial cell line was obtained from the American Type Culture Collection (CRL-3265, ATCC, Manassas, VA, United States) and cultured in Dulbecco’s modified Eagle’s medium (DMEM, HyClone, SH30021) supplemented with 10% fetal bovine serum (FBS, Gibco, 10,270,106), 100 U/ml penicillin and 100 g/ml streptomycin (Gibco, Grand Island, NY, United States).…”
Section: Methodsmentioning
confidence: 99%
“…BV-2 is a commonly used microglial cell line that has been widely used in vitro experiments to explore inflammatory responses in many studies ( Riedl et al, 2009 ; Basso et al, 2017 ; Yoshizaki et al, 2021 ). The BV-2 microglial cell line was obtained from the American Type Culture Collection (CRL-3265, ATCC, Manassas, VA, United States) and cultured in Dulbecco’s modified Eagle’s medium (DMEM, HyClone, SH30021) supplemented with 10% fetal bovine serum (FBS, Gibco, 10,270,106), 100 U/ml penicillin and 100 g/ml streptomycin (Gibco, Grand Island, NY, United States).…”
Section: Methodsmentioning
confidence: 99%
“…It can be inferred that the combined use of Jiaji EA and ganglioside ester may effectively reduce the inhibitory effect on nerve axon growth and further play a protective role on SCI by reducing the signal regulation of Nogo-A, NgR and LINGO-1 gene expression, especially the change of LINGO-1 expression. Considering that there is no effective clinical treatment currently ( Yates et al, 2021 , Yoshizaki et al, 2021 ), our study provided alternative therapeutic strategy for spinal cord injury.…”
Section: Discussionmentioning
confidence: 99%
“…SCI is a serious trauma to the central nervous system, causing serious disability ( Andrade et al, 2021 , Jogia et al, 2021 , Bilchak et al, 2021 ). There is no effective clinical treatment at present ( Yates et al, 2021 , Yoshizaki et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Microglia, the CNS resident macrophages, can shift their functional states between a pro-inflammatory phenotype—characterized by release of inflammatory factors, antigen presentation, and expression of C1q and other markers—to a more neuroprotective phenotype—characterized by phagocytosis of debris and apoptotic cells and expression of S100B and other markers. Similarly, astrocytes display functional heterogeneity under both homeostatic and disease states that may be either neurotoxic or neuroprotective [ 47 , 48 , 49 , 50 ]. Together, microglia and astrocytes can adopt pro- or anti-inflammatory phenotypes to either prevent or exacerbate disease, and studies have shown that reactive microglia and astrocytes contribute to disease through upregulated transcriptional activity of pro-inflammatory genes [ 51 , 52 , 53 ].…”
Section: Cns Immune Regulationmentioning
confidence: 99%